Phanerozoic environments, associations, and deposits. - Laznicka, Peter (Developments in economic geology, 1985)
This is the most comprehensive, all-embracing, single source of data on metallic deposits and their worldwide distribution. With over 1,750 pages it contains: 594 figures illustrating ore styles and their setting; 113 tables providing concise but highly quantitative data on several thousand locality examples; 4 indexes (general, locality, genetic, metals) enabling rapid and thorough searches; and more than 2,000 references. This vast body of information on metallic ore deposits is arranged by environments in which they presently form or lithologic associations in which they occur. The organization of the book follows the approach employed in regional mineral-potential evaluation and exploration. Long-lasting, objectively observable host units and empirical indicators of ore presence are stressed. The coverage is balanced and truly worldwide, based on original literature consulted in over 30 languages and on the author's personal familiarity with more than 2,000 ore deposits located in 85 countries. The book is a must for practising exploration geologists, petrologists, and economic geologists, as well as for specialists in various other branches of geology (e.g. glacial geologists, carbonate sedimentologists, volcanologists, and geochemists). Teachers and students will find this most complete data sourcebook an ideal supplement to the theory and basic data found in textbooks.